2019
DOI: 10.1016/j.jtho.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Heterogeneity of Panel-Based Tumor Mutational Burden in Pulmonary Adenocarcinoma: Separating Biology From Technical Artifacts

Abstract: Background: Tumor mutational burden (TMB) is an emerging biomarker used to identify patients who are more likely to benefit from immuno-oncology therapy. Aside from various unsettled technical aspects, biological variables such as tumor cell content and intratumor heterogeneity may play an important role in determining TMB. Methods: TMB estimates were determined applying the TruSight Oncology 500 targeted sequencing panel. Spatial and temporal heterogeneity was analyzed by multiregion sequencing (two to six sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…This has been emphasized by previous studies which compared TMB values across multiple regions from the same tumour. In 12.5% (3/24) of pulmonary adenocarcinomas [28], 20% (20/100) of NSCLC and 52% (12/23) of urothelial carcinomas [29], the TMB classification was inconsistent across multiple regions. The current study was not powered for adequate subclonality analysis due to its single biopsy sampling approach and panel dataset alone; therefore, subclonal deconstruction is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…This has been emphasized by previous studies which compared TMB values across multiple regions from the same tumour. In 12.5% (3/24) of pulmonary adenocarcinomas [28], 20% (20/100) of NSCLC and 52% (12/23) of urothelial carcinomas [29], the TMB classification was inconsistent across multiple regions. The current study was not powered for adequate subclonality analysis due to its single biopsy sampling approach and panel dataset alone; therefore, subclonal deconstruction is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that heterogeneity across tumor compartments might impact our interpretation of the tumor genome, stressing the fundamental technical differences in computational pipelines and sample characteristics between tTMB and bTMB. 39 Retrospective analysis of samples from the POPLAR study determined that a bTMB cut point of greater than or equal to 16 mutations/sample had the strongest PFS treatment effect and an overall prevalence of 30%. Similarly, data from the OAK study on the groups with bTMB greater than or equal to 16 revealed a significant PFS benefit (HR 0.65 95% CI: 0.47-0.92) from atezolizumab versus docetaxel.…”
Section: Clinical Trial Data Suggesting Use Of Blood Tmb As a Biomarkmentioning
confidence: 99%
“…58 Indel burden, in particular, may be informative in high-TMB cases. 39 Need for Normal Matched Sample. Sequencing of paired tumor-normal matched samples with germline variants removed from the TMB count is regarded as the definitive standard for TMB analysis.…”
Section: From Wes To Large Ngs Panels-comprehensive Genomic Profilingmentioning
confidence: 99%
“…DNA was extracted using a Maxwell 16 Research System (Promega), followed by quantification using the QuBit 2.0 DNA High Sensitivity Kit (Thermo Fisher Scientific). Library preparation for the capture-based TruSight Oncology 500 panel (Illumina) (Supplemental Table 3)was performed as previously described (31). DNA integrity was assessed using the Genomic DNA ScreenTape Analysis on a 4150 TapeStation System (Agilent).…”
mentioning
confidence: 99%